Responsible and Ethical Use of Artificial Intelligence in Language Education: A Systematic Review - Nurkhamimi Zainuddin; Nur Azlin Suhaimi; Mohammad Najib Jaffar; Norita Md Norwawi; Muhammad Sabri Sahrir; Wan Ab Aziz Wan Daud; Mohammad Taufiq Abdul Ghani (Bilingual Publishing Group, 2024)
Indexed by Scopus